Exploring Issues Limiting the Use of Knowledge in Disaster Risk Reduction. - Norton, John; Atun, Funda; Dandoulaki, Miranda (TeMA - Journal of Land Use, Mobility and Environment, 2015)
This paper highlights issues that appear to have hampered the development and use of knowledge and discusses what these imply for applying (or not) the concept of smart cities in different contexts. The conclusions are based on the findings of four sets of work in the context of the KNOW-4-DRR project. From the findings of these activities, it emerges that although there are differences in context, risk and culture, there is a surprising degree of commonality in opinions about why there is insufficient development and application of knowledge for disaster risk reduction, despite the large volumes of information developed on this subject. As regards ICTs, findings suggest that technology, although useful, is not the sole solution for knowledge- based decision making for DRR. In this respect the benefits of smartness in cities are uncertain and depend on the context, where the employment of simpler or more traditional means can be more appropriate for enabling knowledge. A final conclusion is that no matter how useful, knowledge itself is not a panacea for DRR. Decision-making is invariably influenced by conflicting priorities, objectives and constraints, and not necessarily in all stakeholders’ interests or even reflecting their objectives. For example in the midst of the Greek economic crisis, disaster risk awareness and acceptability are becoming less a matter of DRR information and knowledge and must rather be addressed with a view to the new hierarchy of risks (socio-economic, health, emerging) generated by the crisis. However, acknowledging the complexity of the issue should not stand in the way of much needed efforts towards enabling knowledge for DRR with all the tools available in today’s changing world.